ANALISA TEKNIS DAN EKONOMIS SISTEM PERBAIKAN DAUN PROPELLER YANG PATAH PADA KM. MANDIRI DUA TANPA DOCKING - Manik, Parlindungan (Department of Naval Architecture - Diponegoro University, 2009)
At a sailing in a territorial to sea or river, ship propeller frequently collide object or foreign object which float, causing damage at propeller, throw in the form of curving, crack or broken at propeller blade. When this damage do not improve immediately; repaired will generate harm effect to ship construction or parts of machinery. Therefore ship should be immediately to repair (emergency docking) to improve the propeller. But is not easy to get docking space to repair because docking space schedule is very strike, existing graving dock in country. So that ship have to kick one's heels to be able to docking space, which meaning of big loss of time and also expense. The air of this research technical analysis possibility implementation to propeller repairf by floating repair system in territorial water closest with damage location of propeller and compare efficiency economic value and time if repair of propeller done in graving dock or executed by floating repair in graving dock. In this research, repair propeller without docking can be executed by arranging ship trim by arranging ballast tank to be reached space which last for working. Hereinafter worked repair of blade propeller thickly , pitch, aerofoil, wide of blade, obtained mains material type from source which have been collected by either from Owner Surveyor, picture - technique picture and also blade propeller which still goodness. Result of analysis indicate that technically repair of propeller which broken can be executed without docking and economically will be more be efficient up to 700%,in comparison with executed in Graving Dock, and will be more be efficient up to 300% when compared with executed in floating repair system